The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.amjmed.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation-associated Adverse Drug Events

Abstract: Purpose Anticoagulant drugs are among the most common medications that cause adverse drug events (ADEs) in hospitalized patients. We performed a five-year retrospective study at Brigham and Women’s Hospital to determine clinical characteristics, types, root causes, and outcomes of anticoagulant-associated adverse drug events (ADEs). Methods We reviewed all inpatient anticoagulant-associated ADEs, including adverse drug reactions (ADRs) and medication errors, reported at Brigham and Women’s Hospital through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 25 publications
0
80
1
10
Order By: Relevance
“…[14] This study aimed to investigate the effect of computer recording of medical orders on the number of adverse medication events and errors, and was a two-group study with a control group and a higher number of subjects compared to the present study. In another study, the researchers reported positive results in investigation of the effect of interactional education on reduction of medication errors of high-risk drugs in ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…[14] This study aimed to investigate the effect of computer recording of medical orders on the number of adverse medication events and errors, and was a two-group study with a control group and a higher number of subjects compared to the present study. In another study, the researchers reported positive results in investigation of the effect of interactional education on reduction of medication errors of high-risk drugs in ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of the treatment is thromboprophylaxis, usually using Vitamin K antagonists. However, there is no consensus regarding the patient screening criteria and treatment duration because anticoagulant drugs are among the most common medications that cause adverse events 39) . Therefore, in order to select which patients should receive thromboprophylaxis, new biomarkers are needed that would make it possible to identify patients with a pro-thrombotic state and at high risk of clinical events 40) .…”
Section: Discussionmentioning
confidence: 99%
“…Because the authors performed a root cause analysis, they were able to look at the reason why the errors occurred. The most common cause was transcription errors (48%), followed by memory lapses (16.1%) and infusion or parenteral administration problems (8.7%); this is despite the presence of a Medical Information System that integrates online medical records, computerised provider order entries and electronic medication administration records 13. Aside from articles about medication errors in hospital, Fanikos et al focused on adverse drug events and medication errors in hospitalised patients with cardiac issues 14.…”
Section: Ades In the Hospitalmentioning
confidence: 99%